Ductility improvement of cementitious composites reinforced with polyvinyl alcohol-polypropylene hybrid fibers. (March 2016) - Pakravan, Hamid Reza; Latifi, Masoud; Jamshidi, Masoud
This paper investigated the hybridization effect of two chemically different fibers on the flexural behavior of cementitious composite. On this basis, polyvinyl alcohol and polypropylene fibers (polyvinyl alcohol/polypropylene fiber ratios: 75/25%, 50/50%, 100/0% and 0/100%) at different fiber volume fraction contents (1.2% and 2%) were considered as the variables. This study is especially focused on the influence of fiber types and their hybridization on composite deformability. The composite samples are subjected to the three-point bending test after 28 days of curing. The results showed that the fibers increased the flexural strength and ductility of cement matrix. It is revealed that the toughening improvement mechanism of polyvinyl alcohol and polypropylene fibers in cementitious composites are extremely different. Hybridization of polyvinyl alcohol and polypropylene fibers caused no significant improvement on flexural strength, but the strain capacity of composite under flexural load was increased. Finally, it was observed that the replacement of polyvinyl alcohol fiber with 25% volume fraction of polypropylene fibers can be considered as an important method for improving ductility of engineered cementitious composites.